Ethnobotanical study of the medicinal plants used by rural communities in the foothill villages of the Alagar Hills region, Eastern Ghats, Tamil Nadu, India - Muthukrishnan, Shrinitha; Ramachandran, Aruna (Ethnobotany Research and Applications, 2025)
Background: The traditional medicine systems across the world are reliant on the locally available plant species. It is very common for rural communities to treat their diseases using native plant species. This study aimed to document the rich traditional knowledge of medicinal plants used by rural communities in the foothill villages of the Alagar hills region, part of the Eastern Ghats in Tamil Nadu, India. Methods: Ethnobotanical surveys were conducted with 93 informants selected through non-probability sampling and snowball sampling methods distributed across three foothill villages of the Alagar hills region from December 2020 to February 2023. Sociodemographic characteristics of the informants, and ethnobotanical data including plant families, life forms, parts used, modes of administration, and routes of administration were analysed using percentage. Quantitative indices such as Use Value, Family Use Value, Relative Frequency Citation, Informant Consensus Factor, Informant Agreement Ratio, Fidelity Level % were calculated using established formulae. Results: About 199 medicinal plants utilized to treat various disease conditions, grouped into 18 different ailment categories, were documented. The Fabaceae family (31 species) was the most commonly used. Herbs (34%) were the most used life form, and leaves (41%) were the most frequently used plant part in herbal drug preparations. Paste (36%) was the most common preparation method, and the oral route (72%) was the most frequently used route of administration. Conclusions: This study underscores the significant role of medicinal plants in the healthcare practices of rural communities in the study area. Quantitative analysis identified culturally significant species contributing to the conservation of medicinal plant species, preservation of traditional knowledge, and also for isolation and identification of novel bioactive compounds. Keywords: Ethnobotany, Ethnomedicine, Herbal drugs, Dindigul, Traditional knowledge